Persepsi Pelanggan Terhadap Efektivitas Pelayanan Pada PT. Perusahaan Listrik Negara (Persero) Cabang Wawotobi (Studi di Desa Anggotoa Kecamatan Wawotobi Kabupaten Konawe) - Muhamad Irfan Rama (Jayapangus Press, 2018)
This study aims to find out about the public perception of service effectiveness at PT. State Company (Persero) Branch Wawotobi Konawe. The research method used in this research is descriptive qualitative. Informants in this study are employees of PT. PLN Wawotobi Branch and its 138 customers by appointing the Branch Head of Wawotobi as a key informant (key informant). Data taken by interview and field observation while the data analysis used is descriptive qualitative. The public perception of service effectiveness at PT. State Enterprise (Persero) Branch Wawotobi Konawe studied consists of 8 items of clarity of goals to be achieved, clarity of strategy achievement goals, process analysis and policy formulation, planning, formulation of programs, facilities and infrastructure, effective and efficient implementation and supervision system yan educate. From result of research indicate that overall that overall perception of society to effectiveness of service at PT. State Electricity Company (Persero) Wawotobi Konawe branch is quite good average, while things that need to be addressed is the implementation of work that has not been effective and efficient. To know the public perception of service effectiveness at PT. State Electricity Company (Persero) and further research results need to be evaluated and followed up in further scientific research.